Turumba [videorecording] - Kidlat Tahimik; Tellux Films ([Manila] s.n., 1981)
Set in a background Philippine village, the film focuses on one family who traditionally make papier-mache animals to sell during the Turumba festivities. One day a German department store buyer shows up in town and purchases all their stock. When she returns with an order for 500 more (this time with the word "Oktoberfest" painted on them), the family's seasonal occupation becomes year around alienated labor. Of course, they're now able to buy electric fans, TV sets and Beatles records. Our bamboo hut connects with civilization"., the narrator announces with deadpan pride. Increased production however, creates inflated needs. So virtually the entire village has gone to work on a jungle assembly line, turning out papiermache mascots for the Munich Olympics. Long before the local bands learn to play "Deutschland Uber Alles", the fabric of traditional life has been torn asunder.
DVD
Set design, Santi Bose; sound, Ed de Guia.
Keywords: Feature films